High-conductivity and high-strength copper alloy and preparation method thereof
A copper alloy with balanced strength and conductivity is achieved by incorporating reinforcement phases and electroplated carbon fiber, addressing the trade-off in existing alloys through a specific preparation process.
Patent Information
- Application Number
- CN202411148945.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-27
AI Technical Summary
Existing copper alloys face a trade-off between strength and conductivity, with improvements in one property often leading to a decrease in the other, limiting their performance in applications requiring both high strength and high conductivity.
A high-conductivity and high-strength copper alloy is prepared by combining oxygen-free copper with reinforcement phases of Nb, Cr, or Zr, and electroplated copper-coated carbon fiber, using mechanical alloying, repeated melting, rapid solidification, and staged aging treatments to ensure uniform distribution and recrystallization of these phases within the copper matrix.
The resulting copper alloy achieves enhanced tensile strength, conductivity, and high-temperature softening resistance, balancing both properties effectively.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper alloys, and particularly relates to a high-conductivity and high-strength copper alloy and a preparation method thereof. Background Art
[0002] Copper and copper alloys are indispensable basic materials in all walks of life. They have good electrical conductivity, thermal conductivity, corrosion resistance, high plasticity, oxidation resistance and machinability. They have developed into a non-ferrous metal second only to aluminum alloys. They are currently widely used in national defense, military industry, electronics, electrical, petrochemical, transportation, aerospace and other fields.
[0003] High-strength and high-conductivity copper alloys have improved strength and retained good electrical and thermal conductivity on the basis of copper alloys, while also having certain high-temperature softening resistance. At present, high-strength and high-conductivity copper alloys are mainly Cu-Fe series alloys, Cu-Zr series alloys, and Cu-Cr series alloys. However, the strength and conductivity of copper alloys are a pair of contradictions, which are in a state of "one increases while the other decreases". In the copper alloy processing technology, simply improving the material strength or improving the conductivity will mostly reduce the conductivity or strength of the matrix. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a high-conductivity and high-strength copper alloy and a preparation method thereof, aiming to solve at least one technical problem in the background technology.
[0005] The present invention is achieved in that:
[0006] A method for preparing a high-conductivity and high-strength copper alloy, wherein the high-conductivity and high-strength copper alloy is composed of the following components by weight: 1.5% to 6% of a first reinforcement phase, 0.02% to 0.4% of a second reinforcement phase, and the remainder is copper;
[0007] The preparation method comprises the following steps:
[0008] The oxygen-free copper particles and the first reinforcement phase are mixed in proportion, and the mixed material is treated by a mechanical alloying method so that the first reinforcement phase is uniformly embedded in the copper to form a copper alloy;
[0009] The copper alloy is added into a vacuum melting furnace for repeated melting to form a molten copper alloy;
[0010] A second reinforcing phase in powder form is added to obtain a copper alloy composite powder by a rapid solidification method;
[0011] Performing solution treatment and staged aging treatment to obtain the high-conductivity and high-strength copper alloy;
[0012] The first reinforcement phase adopts at least one of Nb, Cr or Zr; and the second reinforcement phase adopts carbon fiber coated with electroplated copper.
[0013] Furthermore, the copper alloy is added into a vacuum melting furnace for repeated melting, specifically as follows:
[0014] Evacuate the vacuum melting furnace, heat until the copper alloy melts, and keep it warm for 8 to 15 minutes;
[0015] Stop heating and wait for the copper alloy to solidify, continue heating to melt the copper alloy, keep warm for 8min to 15min, and repeat this operation at least once.
[0016] Furthermore, the mechanical alloying method uses a high-energy ball mill to grind the mixed material for a time of not less than 20 hours.
[0017] Furthermore, the inner lining of the high-energy ball mill is zirconium oxide, and the grinding medium is zirconium oxide or zirconium beads.
[0018] Furthermore, the solution treatment comprises: heating the copper alloy composite powder to 1000° C. to 1100° C. in a non-oxygen atmosphere, and keeping the temperature for 1 h to 2 h; and rapidly cooling by quenching to form a supersaturated solid solution.
[0019] Furthermore, the specific operation of the segmented aging treatment is as follows:
[0020] Heat the supersaturated solid solution to 100°C to 150°C and keep it warm for 20min to 40min;
[0021] Continue heating to 300℃~350℃, keep warm for 20min~40min;
[0022] Continue heating to 500℃~600℃ and keep warm for 3h~4h.
[0023] Furthermore, the preparation steps of the second reinforcement phase are:
[0024] The carbon fiber powder is placed in a reaction device, heated to 410°C to 430°C in an oxygen atmosphere, and kept warm for 20min to 40min to obtain oxidized carbon fiber;
[0025] In a water bath heating environment at 80°C to 100°C, the oxidized carbon fiber is pickled with an inorganic strong acid for 20min to 40min;
[0026] Using copper salt as electroplating solution, the oxidized carbon fiber after acid leaching is subjected to constant voltage electroplating reaction to obtain electroplated copper-coated carbon fiber mud;
[0027] The carbon fiber powder coated with electroplated copper is prepared by vacuum drying, grinding and sieving.
[0028] The electroplated copper is attached to the surface of the carbon fiber as a coating layer of the carbon fiber, and the thickness of the coating layer is 1 μm to 2 μm.
[0029] Furthermore, the rapid solidification method adopts ultrasonic gas atomization method or centrifugal atomization method.
[0030] The present invention also provides a high-conductivity and high-strength copper alloy prepared by the preparation method.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention adopts batch-wise addition of metal reinforcement phase and electroplated copper-coated carbon fiber reinforcement phase into copper-based materials, combined with a specific process method, to produce a copper alloy with high tensile strength, high softening temperature and high conductivity.
[0033] 2. The present invention adds trace metal elements to the copper matrix, combines mechanical alloying and repeated smelting steps, so that the alloying of oxygen-free copper particles and trace metals is more uniform and sufficient, so that the first reinforcement phase is uniformly present in the copper matrix in the form of Cu-Nb, Cu-Cr, and Cu-Zr precipitation phases, effectively strengthening the copper matrix.
[0034] 3. The present invention uses electroplated copper-coated carbon fiber powder as the second reinforcement phase. Through solution treatment and segmented aging treatment, the electroplated copper-coated carbon fiber of the second reinforcement phase is recrystallized with the copper matrix and dissolved into the copper alloy to greatly increase the conductivity of the copper alloy. At the same time, due to the presence of a coating layer composed of electroplated copper on the outside of the carbon fiber, it can strengthen the effective combination of the carbon fiber and the copper matrix without affecting the density of the material; the segmented aging treatment can increase the strengthening effect of the first reinforcement phase and the second reinforcement phase on the copper matrix. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.
[0036] A method for preparing a high-conductivity and high-strength copper alloy, wherein the high-conductivity and high-strength copper alloy is composed of the following components by weight: 1.5% to 6% of a first reinforcement phase, 0.02% to 0.4% of a second reinforcement phase, and the remainder being copper; wherein the first reinforcement phase is at least one of Nb, Cr or Zr; and the second reinforcement phase is carbon fiber coated with electroplated copper.
[0037] The above preparation method comprises the following steps:
[0038] S1, mixing oxygen-free copper particles and the first reinforcement phase in proportion, and treating the mixture by a mechanical alloying method so that the first reinforcement phase is uniformly embedded in the copper to form a copper alloy;
[0039] Specifically, a stirring, planetary or vibrating high-energy ball mill is used to grind the mixed material for not less than 20 hours. In order to form ultra-fine materials, a spherical grinding medium is filled in the grinding cylinder of the ball mill. In the present invention, the inner lining of the high-energy ball mill is set to zirconium oxide, and the grinding medium is zirconium oxide or zirconium beads, which have high hardness on the one hand and avoid the introduction of impurities into the alloy during the processing process on the other hand.
[0040] The high-energy ball mill grinds the oxygen-free copper particles and the first reinforcement phase (high-purity Nb particles or Cr particles or Zr particles) for a long time. During the grinding process, the copper base and the metal of the first reinforcement phase frequently touch each other, resulting in severe plastic deformation and cold welding. Ultimately, the particles of the first reinforcement phase are evenly embedded in the copper base powder, so that the organization reaches the atomic level and alloying can be achieved; at the same time, an ultra-fine copper alloy is formed, which is conducive to the efficient melting of the alloy during subsequent smelting.
[0041] S2, adding the copper alloy into a vacuum melting furnace for repeated melting to form a molten copper alloy;
[0042] (2.1) Evacuate the vacuum melting furnace, heat until the copper alloy melts, and keep it warm for 8 minutes to 15 minutes;
[0043] (2.2) Stop heating and wait for the copper alloy to solidify. Continue heating to melt the copper alloy and keep it warm for 8 to 15 minutes. Repeat this operation at least once.
[0044] The purpose of this step is to make the alloying of oxygen-free copper particles and the first reinforcement phase more uniform and sufficient, and effectively strengthen the copper matrix; since the melting point of the metal elements of the first reinforcement phase is higher than that of the copper matrix, the method of repeated smelting is adopted to make the first reinforcement phase uniformly exist in the copper matrix as Cu-Nb, Cu-Cr, and Cu-Zr precipitation phases.
[0045] S3, adding a second reinforcing phase of the powder to obtain a copper alloy composite powder by a rapid solidification method;
[0046] A small amount of electroplated copper-coated carbon fiber powder is added to the molten copper alloy obtained in step S2 to form a molten fluid similar to magma, and then the molten fluid is rapidly solidified by ultrasonic gas atomization or centrifugal atomization to form a copper alloy composite powder in which the two are initially fused with each other; in the copper-based composite material, the atomization method, especially the ultrasonic gas atomization method, can quickly and efficiently induce crystal nucleation, enhance the atomic activity and diffusion rate of the alloy elements, and at the same time limit the crystal agglomeration to form fine crystals, so that the first reinforcement phase and the second reinforcement phase are dispersed in the copper matrix;
[0047] On the one hand, this step strengthens the fine grains of the smelted copper alloy, so that the number of Cu-Nb, Cu-Cr, and Cu-Zr precipitated phases formed by the first reinforcement phase increases, which has a dispersion strengthening effect on the copper matrix; on the other hand, the copper alloy + electroplated copper-coated carbon fiber powder are fused to promote the addition of the second reinforcement phase into the copper matrix to form a composite material;
[0048] The electroplated copper-coated carbon fiber powder can be synthesized by itself, and the synthesis method of the present invention is specifically as follows:
[0049] (3.1) placing carbon fiber powder in a reaction device, heating to 410° C. to 430° C. in an oxygen atmosphere, and keeping the temperature for 20 min to 40 min to obtain oxidized carbon fiber;
[0050] The oxidation heating function is to remove the colloid on the surface of the carbon fiber. At the same time, the temperature and time limits are to avoid excessive damage to the carbon fiber surface and affect its mechanical properties.
[0051] (3.2) acid leaching the oxidized carbon fiber with a strong inorganic acid for 20 min to 40 min in a water bath heating environment at 80° C. to 100° C.;
[0052] The purpose of acid immersion is to roughen the surface of the carbon fiber and form a corrosion texture on its surface, which is conducive to the adhesion of subsequent electroplated copper;
[0053] The inorganic strong acid can be sulfuric acid or nitric acid. The following examples use 50% sulfuric acid as an example.
[0054] (3.3) Using copper salt as the electroplating solution, the oxidized carbon fiber after acid leaching is subjected to constant voltage electroplating reaction to obtain electroplated copper-coated carbon fiber mud;
[0055] The electroplating solution mainly uses copper sulfate and other auxiliary reagents, such as sulfuric acid, potassium salt, emulsifier, etc., and other electroplating copper solutions permitted in the art can also be used; the following embodiment selects 100g / L copper sulfate, 60g / L sulfuric acid, 30g / L potassium nitrate, and 0.15g / L emulsifier (OP-10); at a voltage of 2V, electrolysis is performed at room temperature for 3min to 8min. During the electroplating process, copper ions are reduced to copper atoms and deposited on the surface of carbon fibers to form electroplated copper. The thickness of the electrolytic copper can be controlled by parameters such as the electroplating solution composition and the electrolysis time;
[0056] (3.4) vacuum drying, grinding, and sieving to obtain electroplated copper-coated carbon fiber powder;
[0057] The copper-plated carbon fiber mud obtained in step (3.3) is separated from the electroplating liquid, and then cleaned with ethanol or water, and dried completely in a vacuum drying oven; then ground by a grinder to prevent the powder from agglomerating, and sieved to form a copper-plated carbon fiber powder with uniform particles;
[0058] Electroplated copper is attached to the surface of the carbon fiber as a coating layer of the carbon fiber. The thickness of the coating layer is 1 μm to 2 μm. The reason for controlling the thickness is to avoid excessive thickness and easy peeling.
[0059] In this step, the electroplated copper-coated carbon fiber powder is used as the second reinforcement phase, and is combined with the copper alloy by a rapid solidification method and subsequent solution treatment and segmented aging treatment, thereby preventing the carbon fiber from destroying the integrity of the copper alloy system lattice.
[0060] S4, performing a solution treatment and a stepwise aging treatment to obtain the high-conductivity and high-strength copper alloy;
[0061] (4.1) Solution treatment includes:
[0062] In a non-oxygen atmosphere, the copper alloy composite powder is heated to 1000°C to 1100°C and kept at this temperature for 1h to 2h; the powder is quenched and rapidly cooled to form a supersaturated solid solution;
[0063] (4.2) The specific operations of the segmented aging treatment are as follows:
[0064] Heat the supersaturated solid solution to 100°C to 150°C and keep it warm for 20min to 40min;
[0065] Continue heating to 300℃~350℃, keep warm for 20min~40min;
[0066] Continue heating to 500℃~600℃ and keep warm for 3h~4h.
[0067] Although conventional carbon fibers have strong conductivity and strength, when combined with copper alloys, they will reduce the strength and conductivity of the alloy. The reason is that after the addition of carbon fibers to the copper matrix, the density of the copper matrix is reduced, and the carbon fibers tend to agglomerate, which increases the porosity of the copper matrix, reduces the activity of copper atoms, and prevents the diffusion of copper atoms, destroying the metal copper lattice system, thereby affecting the strength and conductivity of the copper matrix.
[0068] The present invention uses electroplated copper-coated carbon fiber powder as the second reinforcement phase, and through solid solution treatment and segmented aging treatment, the electroplated copper-coated carbon fiber of the second reinforcement phase and the copper matrix are recrystallized, so that the second reinforcement phase is dissolved in the copper alloy to form a composite copper alloy, which can greatly increase the conductivity of the copper alloy. At the same time, due to the presence of a coating layer composed of electroplated copper on the outside of the carbon fiber, it can strengthen the effective combination of the carbon fiber and the copper matrix without affecting the density of the material; the segmented aging treatment can increase the strengthening effect of the first reinforcement phase and the second reinforcement phase on the copper matrix.
[0069] Example 1
[0070] A method for preparing a high-conductivity and high-strength copper alloy comprises the following steps:
[0071] Step (1) Prepare the raw materials
[0072] The carbon fiber powder was heated at 410°C for 40 minutes in an oxygen atmosphere, and then acid-leached in 50% sulfuric acid at 80°C water bath for 40 minutes; 100g / L copper sulfate, 60g / L sulfuric acid, 30g / L potassium nitrate, and 0.15g / L emulsifier (OP-10) were used as electroplating solution; the acid-leached carbon fiber was electrolyzed at room temperature for 3 minutes at a voltage of 2V; solid-liquid separation was performed, and then it was cleaned with ethanol or water, and placed in a vacuum drying oven to dry completely; then it was ground by a grinder and sieved to form a carbon fiber powder coated with electroplated copper with uniform particles, and the thickness of the electroplated copper layer was about 1.02μm;
[0073] According to the weight ratio, 4% high-purity Nb particles, 0.2% electroplated copper-coated carbon fiber powder, and 95.8% oxygen-free copper particles are configured;
[0074] Step (2) mixing oxygen-free copper particles and high-purity Nb particles, and grinding the mixture for 24 hours using a stirring high-energy ball mill, so that the Nb element is uniformly embedded in the copper to form a Cu-Nb alloy; the inner lining and grinding medium of the high-energy ball mill are both made of zirconium oxide;
[0075] Step (3) Add the ground Cu-Nb alloy into a vacuum melting furnace and evacuate the furnace to set the vacuum degree to 6×10 -3 Pa, heat the copper alloy to about 1400℃ to melt it, keep it warm for 8min; stop heating and wait for the copper alloy to solidify, continue heating to melt it, keep it warm for 8min, repeat this operation 2 times, that is, repeat smelting 4 times;
[0076] Step (4) adding electroplated copper-coated carbon fiber powder to the molten Cu-Nb alloy obtained in step (3) to obtain a copper alloy composite powder by ultrasonic gas atomization;
[0077] Step (5) heating the copper alloy composite powder to 1000° C. in a vacuum environment and keeping the temperature for 2 hours; quenching and rapidly cooling to form a supersaturated solid solution;
[0078] Step (6) heating the supersaturated solid solution to 100° C. and keeping it warm for 40 minutes; continuing to heat it to 300° C. and keeping it warm for 40 minutes; continuing to heat it to 500° C. and keeping it warm for 4 hours; and naturally cooling it to obtain a high-conductivity and high-strength copper alloy.
[0079] Example 2
[0080] A method for preparing a high-conductivity and high-strength copper alloy comprises the following steps:
[0081] Step (1) Prepare the raw materials
[0082] The carbon fiber powder was heated at 420°C for 30 minutes in an air atmosphere, and then placed in 50% sulfuric acid for acid leaching at 90°C water bath for 30 minutes; 100g / L copper sulfate, 60g / L sulfuric acid, 30g / L potassium nitrate, and 0.15g / L emulsifier (OP-10) were used as electroplating solution; the acid-leached carbon fiber was electrolyzed at room temperature for 4 minutes at a voltage of 2V; solid-liquid separation was performed, and then it was cleaned with ethanol or water, and placed in a vacuum drying oven for complete drying; then it was ground by a grinder to prevent the powder from agglomerating into blocks, and sieved to form a uniformly granulated copper-coated carbon fiber powder, and the thickness of the electroplated copper layer was about 1.33μm;
[0083] The raw materials are configured according to the weight ratio: 4.0% high-purity Cr particles, 0.2% electroplated copper-coated carbon fiber powder, and 95.8% oxygen-free copper particles;
[0084] Step (2) mixing oxygen-free copper particles and high-purity Cr particles, and grinding the mixture for 30 hours using a vibrating high-energy ball mill so that the Cr element is evenly embedded in the copper to form a Cu-Cr alloy; the inner lining of the high-energy ball mill is zirconium oxide, and the grinding medium is zirconium beads;
[0085] Step (3) Add the ground Cu-Cr alloy into a vacuum melting furnace and evacuate the furnace to set the vacuum degree to 6×10 -3 Pa, heat the copper alloy to about 1360℃ to melt it, keep it warm for 10min; stop heating and wait for the copper alloy to solidify, continue heating to melt it, keep it warm for 10min, repeat this operation 2 times, that is, repeat smelting 4 times;
[0086] Step (4) adding electroplated copper-coated carbon fiber powder to the molten Cu-Cr alloy obtained in step (3) to obtain a copper alloy composite powder by centrifugal atomization;
[0087] Step (5) heating the copper alloy composite powder to 1050° C. under a vacuum environment and keeping the temperature for 1.5 hours; quenching and rapidly cooling to form a supersaturated solid solution;
[0088] Step (6) heating the supersaturated solid solution to 130° C. and keeping it warm for 30 minutes; continuing to heat it to 330° C. and keeping it warm for 30 minutes; continuing to heat it to 550° C. and keeping it warm for 3.5 hours; and naturally cooling it to obtain a high-conductivity and high-strength copper alloy.
[0089] Example 3
[0090] A method for preparing a high-conductivity and high-strength copper alloy comprises the following steps:
[0091] Step (1) Prepare the raw materials
[0092] The carbon fiber powder was heated at 430°C for 20 minutes in an air atmosphere, and then placed in 50% sulfuric acid for acid leaching at 100°C water bath for 20 minutes; 100g / L copper sulfate, 60g / L sulfuric acid, 30g / L potassium nitrate, and 0.15g / L emulsifier (OP-10) were used as electroplating solution; the acid-leached carbon fiber was electrolyzed at room temperature for 8 minutes at a voltage of 2V; solid-liquid separation was performed, and then it was cleaned with ethanol or water, and placed in a vacuum drying oven for complete drying; then it was ground by a grinder to prevent the powder from agglomerating into blocks, and sieved to form a carbon fiber powder coated with electroplated copper with uniform particles, and the thickness of the electroplated copper layer was about 1.97μm;
[0093] The raw materials are configured according to the weight ratio: 4.0% high-purity Zr particles, 0.2% electroplated copper-coated carbon fiber powder, and 95.8% oxygen-free copper particles;
[0094] Step (2) mixing oxygen-free copper particles and high-purity Zr particles, and grinding the mixture for 30 hours using a stirring high-energy ball mill, so that the Zr element is evenly embedded in the copper to form a Cu-Zr alloy; the inner lining and grinding medium of the high-energy ball mill are made of zirconium oxide;
[0095] Step (3) Add the ground Cu-Zr alloy into a vacuum melting furnace and evacuate the furnace to set the vacuum degree to 6×10 -3 Pa, heat the copper alloy to about 1500℃ to melt it, keep it warm for 15min; stop heating and wait for the copper alloy to solidify, continue heating to melt it, keep it warm for 15min, repeat this operation 2 times, that is, repeat smelting 4 times;
[0096] Step (4) adding electroplated copper-coated carbon fiber powder to the molten Cu-Zr alloy obtained in step (3) to obtain a copper alloy composite powder by centrifugal atomization;
[0097] Step (5) heating the copper alloy composite powder to 1100° C. in a vacuum environment and keeping the temperature for 1 hour; quenching and rapidly cooling to form a supersaturated solid solution;
[0098] Step (6) heating the supersaturated solid solution to 150° C. and keeping it warm for 20 minutes; continuing to heat it to 350° C. and keeping it warm for 20 minutes; continuing to heat it to 600° C. and keeping it warm for 3 hours; and naturally cooling it to obtain a high-conductivity and high-strength copper alloy.
[0099] Example 4
[0100] A method for preparing a high-conductivity and high-strength copper alloy comprises the following steps:
[0101] Step (1) Prepare the raw materials
[0102] The carbon fiber powder was heated at 430°C for 20 minutes in an air atmosphere, and then acid-leached in 50% sulfuric acid at 100°C water bath for 20 minutes; 100g / L copper sulfate, 60g / L sulfuric acid, 30g / L potassium nitrate, and 0.15g / L emulsifier (OP-10) were used as electroplating solution; the acid-leached carbon fiber was electrolyzed at room temperature for 6 minutes at a voltage of 2V; solid-liquid separation was performed, and then it was cleaned with ethanol or water, and dried completely in a vacuum drying oven; then it was ground by a grinder to prevent the powder from agglomerating into blocks, and sieved to form a carbon fiber powder coated with electroplated copper with uniform particles, and the thickness of the electroplated copper layer was about 1.61μm;
[0103] The raw materials are configured according to the weight ratio: 2.0% high-purity Cr particles, 2% high-purity Zr particles, 0.2% electroplated copper-coated carbon fiber powder, and 95.8% oxygen-free copper particles;
[0104] Step (2) mixing oxygen-free copper particles, high-purity Cr particles, and high-purity Zr particles, and grinding the mixture for 30 hours using a stirring high-energy ball mill, so that the Cr and Zr elements are uniformly embedded in the copper to form a Cu-Cr-Zr alloy; the inner lining and grinding medium of the high-energy ball mill are made of zirconium oxide;
[0105] Step (3) Add the ground Cu-Cr-Zr alloy into a vacuum melting furnace, evacuate the furnace, and set the vacuum degree to 6×10 -3 Pa, heat the copper alloy to about 1460℃ to melt it, keep it warm for 12 minutes; stop heating and wait for the copper alloy to solidify, continue heating to melt it, keep it warm for 15 minutes, repeat this operation 3 times, that is, repeat smelting 5 times;
[0106] Step (4) adding electroplated copper-coated carbon fiber powder to the molten Cu-Cr-Zr alloy obtained in step (3) to obtain a copper alloy composite powder by centrifugal atomization;
[0107] Step (5) heating the copper alloy composite powder to 1100° C. in a vacuum environment and keeping the temperature for 1 hour; quenching and rapidly cooling to form a supersaturated solid solution;
[0108] Step (6) heating the supersaturated solid solution to 150° C. and keeping it warm for 20 minutes; continuing to heat it to 350° C. and keeping it warm for 20 minutes; continuing to heat it to 600° C. and keeping it warm for 3 hours; and naturally cooling it to obtain a high-conductivity and high-strength copper alloy.
[0109] Example 5
[0110] A method for preparing a high-conductivity and high-strength copper alloy comprises the following steps:
[0111] Step (1) Prepare the raw materials
[0112] The same steps as in Example 4 were used to prepare electroplated copper-coated carbon fiber powder with uniform particles;
[0113] The raw materials are configured according to the weight ratio: 2.0% high-purity Nb particles, 2% high-purity Zr particles, 0.2% electroplated copper-coated carbon fiber powder, and 95.8% oxygen-free copper particles;
[0114] Step (2) mixing oxygen-free copper particles, high-purity Nb particles, and high-purity Zr particles, and grinding the mixture for 40 hours using a stirring high-energy ball mill, so that Zr and Nb elements are uniformly embedded in the copper to form a Cu-Nb-Zr alloy; the inner lining and grinding medium of the high-energy ball mill are made of zirconium oxide;
[0115] Step (3) Add the ground Cu-Nb-Zr alloy into a vacuum melting furnace and evacuate the furnace to set the vacuum degree to 6×10 -3 Pa, heat the copper alloy to about 1400℃ to melt it, and keep it warm for 12 minutes; stop heating and wait for the copper alloy to solidify, continue heating to melt the copper alloy, and keep it warm for 12 minutes, and repeat this operation 3 times, that is, repeat smelting 5 times;
[0116] Step (4) adding electroplated copper-coated carbon fiber powder to the molten Cu-Nb-Zr alloy obtained in step (3) to obtain a copper alloy composite powder by centrifugal atomization;
[0117] Step (5) heating the copper alloy composite powder to 1050° C. under a vacuum environment and keeping the temperature for 1 hour; quenching and rapidly cooling to form a supersaturated solid solution;
[0118] Step (6) heating the supersaturated solid solution to 150° C. and keeping it warm for 20 minutes; continuing to heat it to 350° C. and keeping it warm for 20 minutes; continuing to heat it to 600° C. and keeping it warm for 3 hours; and naturally cooling it to obtain a high-conductivity and high-strength copper alloy.
[0119] Example 6
[0120] A method for preparing a high-conductivity and high-strength copper alloy comprises the following steps:
[0121] Step (1) Prepare the raw materials
[0122] The same steps as in Example 4 were used to prepare carbon fiber powder with uniform particles coated with electroplated copper, and the thickness of the electroplated copper layer was about 1.61 μm;
[0123] The raw materials are configured according to the weight ratio: 2.0% high-purity Nb particles, 2% high-purity Cr particles, 0.2% electroplated copper-coated carbon fiber powder, and 95.8% oxygen-free copper particles;
[0124] Step (2) mixing oxygen-free copper particles, high-purity Nb particles, and high-purity Cr particles, and grinding the mixture for 40 hours using a stirring high-energy ball mill, so that the Cr and Nb elements are uniformly embedded in the copper to form a Cu-Nb-Cr alloy; the inner lining and grinding medium of the high-energy ball mill are made of zirconium oxide;
[0125] Step (3) Add the ground Cu-Nb-Cr alloy into a vacuum melting furnace and evacuate the furnace to set the vacuum degree to 6×10 -3 Pa, heat the copper alloy to about 1360℃ to melt it, keep it warm for 12min; stop heating and wait for the copper alloy to solidify, continue heating to melt it, keep it warm for 12min, repeat this operation 3 times, that is, repeat smelting 5 times;
[0126] Step (4) adding electroplated copper-coated carbon fiber powder to the molten Cu-Nb-Cr alloy obtained in step (3) to obtain a copper alloy composite powder by centrifugal atomization;
[0127] Step (5) heating the copper alloy composite powder to 1050° C. under a vacuum environment and keeping the temperature for 1 hour; quenching and rapidly cooling to form a supersaturated solid solution;
[0128] Step (6) heating the supersaturated solid solution to 150° C. and keeping it warm for 20 minutes; continuing to heat it to 350° C. and keeping it warm for 20 minutes; continuing to heat it to 600° C. and keeping it warm for 3 hours; and naturally cooling it to obtain a high-conductivity and high-strength copper alloy.
[0129] Example 7
[0130] A method for preparing a high-conductivity and high-strength copper alloy comprises the following steps:
[0131] Step (1) Prepare the raw materials
[0132] The same steps as in Example 4 were used to prepare carbon fiber powder with uniform particles coated with electroplated copper, and the thickness of the electroplated copper layer was about 1.61 μm;
[0133] The raw materials are configured according to the weight ratio: 1% high-purity Nb particles, 1.5% high-purity Cr particles, 1.5% high-purity Zr particles, 0.2% electroplated copper-coated carbon fiber powder, and 95.8% oxygen-free copper particles;
[0134] Step (2) mixing oxygen-free copper particles, high-purity Nb particles, and high-purity Cr particles, and grinding the mixture for 40 hours using a stirring high-energy ball mill, so that Zr, Cr, and Nb elements are uniformly embedded in the copper to form a Cu-Nb-Cr-Z alloy; the inner lining and grinding medium of the high-energy ball mill are made of zirconium oxide;
[0135] Step (3) Add the ground Cu-Nb-Cr-Zr alloy into a vacuum melting furnace, evacuate the furnace, and set the vacuum degree to 6×10-3 Pa, heat the copper alloy to about 1460℃ to melt it, and keep it warm for 12 minutes; stop heating and wait for the copper alloy to solidify, continue heating to melt the copper alloy, and keep it warm for 12 minutes, and repeat this operation 4 times, that is, smelting repeatedly 6 times;
[0136] Step (4) adding electroplated copper-coated carbon fiber powder to the molten Cu-Nb-Cr-Zr alloy obtained in step (3) to obtain a copper alloy composite powder by centrifugal atomization;
[0137] Step (5) heating the copper alloy composite powder to 1050° C. under a vacuum environment and keeping the temperature for 1 hour; quenching and rapidly cooling to form a supersaturated solid solution;
[0138] Step (6) heating the supersaturated solid solution to 150° C. and keeping it warm for 20 minutes; continuing to heat it to 350° C. and keeping it warm for 20 minutes; continuing to heat it to 600° C. and keeping it warm for 3 hours; and naturally cooling it to obtain a high-conductivity and high-strength copper alloy.
[0139] Example 8
[0140] This embodiment is a method for preparing a high-conductivity and high-strength copper alloy. The only difference from Embodiment 1 is the dosage of the second reinforcement phase, which is set to 0.02% of electroplated copper-coated carbon fiber powder in this embodiment.
[0141] Example 9
[0142] This embodiment is a method for preparing a high-conductivity and high-strength copper alloy. The only difference from Embodiment 1 is the dosage of the second reinforcement phase, which is set to 0.05% of electroplated copper-coated carbon fiber powder.
[0143] Example 10
[0144] This embodiment is a method for preparing a high-conductivity and high-strength copper alloy. The only difference from Embodiment 1 is the dosage of the second reinforcement phase, which is set to 0.1% of electroplated copper-coated carbon fiber powder.
[0145] Embodiment 11
[0146] This embodiment is a method for preparing a high-conductivity and high-strength copper alloy. The only difference from Embodiment 1 is the dosage of the second reinforcement phase, which is set to 0.4% of electroplated copper-coated carbon fiber powder.
[0147] Example 12
[0148] This embodiment is a method for preparing a high-conductivity and high-strength copper alloy. The only difference from Embodiment 1 is the dosage of the first reinforcement phase, which is set to 1.5% of high-purity Nb particles.
[0149] Embodiment 13
[0150] This embodiment is a method for preparing a high-conductivity and high-strength copper alloy. The only difference from Embodiment 1 is the dosage of the first reinforcement phase, which is set to 3% of high-purity Nb particles in this embodiment.
[0151] Embodiment 14
[0152] This embodiment is a method for preparing a high-conductivity and high-strength copper alloy. The only difference from Embodiment 1 is the dosage of the first reinforcement phase, which is set to 6% of high-purity Nb particles.
[0153] Embodiment 15
[0154] This embodiment is a method for preparing a high-conductivity and high-strength copper alloy. The only difference from Embodiment 1 is the number of repeated smelting times in step (3). In this embodiment, the total number of smelting times is set to 3 times.
[0155] Comparative Example 1
[0156] This comparative example is a method for preparing a high-conductivity and high-strength copper alloy, which differs from Example 1 in that the second reinforcement phase is deleted; the specific steps are as follows:
[0157] Step (1) according to the weight ratio, 4% of high-purity Nb particles and 95.8% of oxygen-free copper particles are prepared;
[0158] Step (2) mixing oxygen-free copper particles and high-purity Nb particles, and grinding the mixture for 24 hours using a stirring high-energy ball mill, so that the Nb element is uniformly embedded in the copper to form a Cu-Nb alloy; the inner lining and grinding medium of the high-energy ball mill are made of zirconium oxide;
[0159] Step (3) Add the ground Cu-Nb alloy into a vacuum melting furnace and evacuate the furnace to set the vacuum degree to 6×10 -3 Pa, heat the copper alloy to about 1400℃ to melt it, keep it warm for 8min; stop heating and wait for the copper alloy to solidify, continue heating to melt it, keep it warm for 8min, repeat this operation 2 times;
[0160] Step (4) preparing copper alloy composite powder by ultrasonic gas atomization of the molten Cu-Nb alloy prepared in step (3);
[0161] Step (5) heating the copper alloy composite powder to 1000° C. in a vacuum environment and keeping the temperature for 2 hours; quenching and rapidly cooling to form a supersaturated solid solution;
[0162] Step (6) heating the supersaturated solid solution to 100° C. and keeping it warm for 40 minutes; continuing to heat it to 300° C. and keeping it warm for 40 minutes; continuing to heat it to 500° C. and keeping it warm for 4 hours; and naturally cooling it to obtain a high-conductivity and high-strength copper alloy.
[0163] Comparative Example 2
[0164] This comparative example is a method for preparing a high-conductivity and high-strength copper alloy, which differs from Example 1 in the composite method of the second reinforcement phase and the copper alloy; the specific steps are as follows:
[0165] Step (1), preparing raw materials, the same as in Example 1;
[0166] Step (2), same as in Example 1, to obtain a Cu-Nb alloy;
[0167] Step (3), adding the ground Cu-Nb alloy and the electroplated copper-coated carbon fiber powder into a vacuum melting furnace, evacuating the furnace to a vacuum degree of 6×10 -3 Pa, heat the copper alloy to about 1400℃ to melt it, keep it warm for 8 minutes; stop heating and wait for the copper alloy to solidify, continue heating to melt it, keep it warm for 8 minutes, repeat this operation twice;
[0168] Step (4), preparing copper alloy composite powder by ultrasonic gas atomization method;
[0169] Step (5) is the same as in Example 1;
[0170] Step (6) is the same as in Example 1.
[0171] Comparative Example 3
[0172] This comparative example is a method for preparing a high-conductivity and high-strength copper alloy. The difference from Example 1 lies in the material of the second reinforcement phase. This comparative example uses conventional carbon fiber powder.
[0173] Comparative Example 4
[0174] This comparative example is a method for preparing a high-conductivity and high-strength copper alloy. The difference from Example 1 is that the method for preparing the copper alloy composite powder by the rapid solidification method in step (4) is deleted, and the solid solution treatment is directly performed.
[0175] Comparative Example 5
[0176] This comparative example is a method for preparing a high-conductivity and high-strength copper alloy. The difference from Example 1 lies in the aging treatment step in step (6), which is as follows:
[0177] The supersaturated solid solution is heated to 500°C and kept at this temperature for 5.5 hours; after natural cooling, a high-conductivity and high-strength copper alloy is obtained.
[0178] The high-conductivity and high-strength copper alloys obtained in Examples 1 to 15 and Comparative Examples 1 to 5 were press-formed, and then the tensile strength, conductivity, softening temperature and other properties were tested. The results are shown in Table 1.
[0179] Tensile strength: The tensile strength of the alloy is tested in accordance with GB / T 24182-2009 standard requirements.
[0180] Electrical conductivity: The electrical conductivity of copper alloys is expressed in International Annealed Copper Standard (%IACS) units.
[0181] Softening temperature: Test the softening temperature of the alloy in accordance with GB / T 5989-2023 standard.
[0182] Table 1
[0183] Test subjects Tensile strength MPa Conductivity %IACS Softening temperature / ℃ Example 1 761 85.9 657 Example 2 766 85.7 659 Example 3 760 85.8 655 Example 4 788 86.3 671 Example 5 795 86.3 673 Example 6 791 86.2 669 Example 7 815 87.3 677 Example 8 757 83.8 658 Example 9 759 84.7 658 Example 10 760 85.1 661 Embodiment 11 757 85.9 653 Example 12 751 85.0 613 Example 13 777 85.5 625 Embodiment 14 793 85.5 653 Embodiment 15 755 85.8 651 Comparative Example 1 757 75.5 655 Comparative Example 2 750 76.4 650 Comparative Example 3 771 73.2 672 Comparative Example 4 690 83.2 611 Comparative Example 5 733 81.7 623
[0184] Examples 1 to 3 use a single metal reinforcement phase, and its compressive strength is not less than 760 MPa and its conductivity is not less than 85.5% IACS; Examples 4 to 6 use two metal reinforcement phases, and Example 7 uses three metal reinforcement phases. It can be seen from the strengthening effect data that three metal reinforcement phases > two metal reinforcement phases > single metal reinforcement phase.
[0185] Compared with Example 1, Examples 8 to 11 change the amount of the second reinforcement phase. As the amount of the second reinforcement phase increases, the conductivity also increases, and the compressive strength and softening temperature remain basically stable with a slight increase. However, when the amount of the second reinforcement phase increases to a certain amount, the conductivity enhancement effect is not obvious, and the compressive strength and softening temperature decrease slightly, so it is set to 0.02-0.4%.
[0186] Compared with Example 1, Examples 12 to 14 change the amount of the first reinforcing phase. As the amount of the first reinforcing phase increases, the compressive strength and softening temperature increase significantly, and the conductivity changes little. After increasing to a certain amount, the conductivity decreases slightly, so it is set to 1.5-6%.
[0187] Compared with Example 1, Example 15 reduces the number of times the first reinforcement phase and copper are smelted. It can be seen that its compressive strength and softening temperature are reduced.
[0188] From the comparison data between Comparative Example 1 and Example 1, it can be seen that without adding the second reinforcement phase, its compressive strength and softening temperature are only slightly reduced, but the electrical conductivity is reduced by 10.4% IACS.
[0189] From the comparison data of Comparative Example 2 and Example 1, it can be seen that the compressive strength and softening temperature of the first reinforcement phase, the second reinforcement phase and the copper matrix are mixed and smelted, and the compressive strength and softening temperature are only slightly reduced, but the electrical conductivity is reduced by 9.5% IACS.
[0190] From the comparison data of Comparative Example 3 and Example 1, it can be seen that the use of conventional carbon fiber as the second reinforcement phase improves the compressive strength and softening temperature, but the conductivity decreases by 12.7% IACS. The reason should be that the carbon fiber enters the copper matrix and destroys its lattice integrity, causing lattice distortion and increasing resistance.
[0191] From the comparison data of Comparative Example 4 and Example 1, it can be seen that when conventional carbon fiber is used as the second reinforcement phase, its electrical conductivity is only slightly reduced (2.7% IACS), but the compressive strength is reduced by 71 MPa and the softening temperature is significantly reduced. The reason is that the rapid solidification method used in the present invention before solution treatment is beneficial to grain refinement and improve alloy strength.
[0192] From the comparison data of Comparative Example 5 and Example 1, it can be seen that the strengthening effect of the segmented aging treatment on the strength, softening temperature and conductivity of the alloy is better than the conventional aging treatment in Comparative Example 5, especially the compressive strength and softening temperature.
[0193] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a high-conductivity and high-strength copper alloy, characterized in that: The high-conductivity and high-strength copper alloy is composed of the following components by weight: 1.5% to 6% of the first reinforcement phase, 0.02% to 0.4% of the second reinforcement phase, and the balance is copper; The preparation method comprises the following steps: The oxygen-free copper particles and the first reinforcement phase are mixed in proportion, and the mixed material is treated by a mechanical alloying method so that the first reinforcement phase is uniformly embedded in the copper to form a copper alloy; The copper alloy is added into a vacuum melting furnace for repeated melting to form a molten copper alloy; Adding the second reinforcing phase in powder form, and preparing copper alloy composite powder by a rapid solidification method; Performing solution treatment and staged aging treatment to obtain the high-conductivity and high-strength copper alloy; The first reinforcement phase adopts at least one of Nb, Cr or Zr; and the second reinforcement phase adopts carbon fiber coated with electroplated copper.
2. The method for preparing a high-conductivity and high-strength copper alloy according to claim 1, characterized in that: The copper alloy is added into the vacuum melting furnace for repeated melting, specifically as follows: Evacuate the vacuum melting furnace, heat until the copper alloy melts, and keep it warm for 8 to 15 minutes; Stop heating and wait for the copper alloy to solidify, continue heating to melt the copper alloy, keep warm for 8min to 15min, and repeat this operation at least once.
3. The method for preparing a high-conductivity and high-strength copper alloy according to claim 1, characterized in that: The mechanical alloying method uses a high-energy ball mill to grind the mixed material for a time of not less than 20 hours.
4. The method for preparing a high-conductivity and high-strength copper alloy according to claim 3, characterized in that: The inner lining of the high energy ball mill is zirconium oxide, and the grinding medium is zirconium oxide or zirconium beads.
5. The method for preparing a high-conductivity and high-strength copper alloy according to claim 1, characterized in that: The solid solution treatment comprises: heating the copper alloy composite powder to 1000° C. to 1100° C. in a non-oxygen atmosphere, and keeping the temperature for 1 hour to 2 hours; and quenching and rapidly cooling to form a supersaturated solid solution.
6. The method for preparing a high-conductivity and high-strength copper alloy according to claim 5, characterized in that: The specific operation of the segmented aging treatment is as follows: Heat the supersaturated solid solution to 100°C to 150°C and keep it warm for 20min to 40min; Continue heating to 300℃~350℃, keep warm for 20min~40min; Continue heating to 500℃~600℃ and keep warm for 3h~4h.
7. The method for preparing a high-conductivity and high-strength copper alloy according to claim 1, characterized in that: The preparation steps of the second reinforcement phase are: The carbon fiber powder is placed in a reaction device, heated to 410°C to 430°C in an oxygen atmosphere, and kept warm for 20min to 40min to obtain oxidized carbon fiber; In a water bath heating environment at 80°C to 100°C, the oxidized carbon fiber is pickled with an inorganic strong acid for 20min to 40min; Using copper salt as electroplating solution, the oxidized carbon fiber after acid leaching is subjected to constant voltage electroplating reaction to obtain electroplated copper-coated carbon fiber mud; The carbon fiber powder coated with electroplated copper is prepared by vacuum drying, grinding and sieving. The electroplated copper is attached to the surface of the carbon fiber as a coating layer of the carbon fiber, and the thickness of the coating layer is 1 μm to 2 μm.
8. The method for preparing a high-conductivity and high-strength copper alloy according to claim 1, characterized in that: The rapid solidification method adopts ultrasonic gas atomization method or centrifugal atomization method.
9. The high-conductivity and high-strength copper alloy prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Cited By
High-conductivity copper alloy wire and preparation process thereof
CN121826428A
Highly conductive copper alloy wire and process for making same
CN121826428B
